Implementation of Smart Models to Improve Student Activities and Learning Outcomes - Mohammed Mahdianur, Desi Dvitalia Saari (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
The problem in this study is the low activity and learning outcomes of students at SDN Kelayan Selatan 3. The purpose of this study is to describe teacher activities, analyze student activities and student learning outcomes. This study uses a qualitative approach with the type of Classroom Action Research (PTK), with 4 meetings. The setting of this research is grade IV students in the even semester of SDN Kelayam Selatan 3 for the 2022/2023 academic year. The results of the research that have been carried out show that the teacher's activity in meeting 1 reached 75% of the "Good" criterion and always increased so that in meeting 4 it reached 100% of the "Very Good" criterion. Student activity in meeting 1 reached 82%, and increased in meeting 4 reaching 100%. The classical completeness of student learning outcomes in meeting 1 reached 48% and also increased until meeting 4 reached 100%. Based on the results of the study, it can be concluded that teacher activities, student activities and learning outcomes in using the PINTAR model have been carried out in accordance with the steps of the model.